2017
DOI: 10.1021/acs.est.7b03332
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies and Uncertainties in Bottom-up Gridded Inventories of Livestock Methane Emissions for the Contiguous United States

Abstract: In this analysis we used a spatially explicit, simplified bottom-up approach, based on animal inventories, feed dry matter intake, and feed intake-based emission factors to estimate county-level enteric methane emissions for cattle and manure methane emissions for cattle, swine, and poultry for the contiguous United States. Overall, this analysis yielded total livestock methane emissions (8916 Gg/yr; lower and upper 95% confidence bounds of ±19.3%) for 2012 (last census of agriculture) that are comparable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
4
23
0
1
Order By: Relevance
“…For example, Cui et al () applied airborne measurements over the San Joaquin Valley to infer regional methane sources that were 1.7 times the bottom‐up estimates, with livestock accounting for ~75% of the total flux. Hristov et al () showed that current inventories differed significantly in their spatial allocation of agricultural methane emissions: within the contiguous United States, the Emission Database for Global Atmospheric Research v4.2 FT2010 (EDGAR, ) and Gridded Environmental Protection Agency (EPA) (Maasakkers et al, ) estimates correlated to only R 2 = 0.1 and 0.5 for manure and enteric fluxes, respectively. Hristov et al () further developed a county‐level emission inventory based on animal population, with some of the largest discrepancies relative to existing inventories occurring over our study region, the Upper Midwest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cui et al () applied airborne measurements over the San Joaquin Valley to infer regional methane sources that were 1.7 times the bottom‐up estimates, with livestock accounting for ~75% of the total flux. Hristov et al () showed that current inventories differed significantly in their spatial allocation of agricultural methane emissions: within the contiguous United States, the Emission Database for Global Atmospheric Research v4.2 FT2010 (EDGAR, ) and Gridded Environmental Protection Agency (EPA) (Maasakkers et al, ) estimates correlated to only R 2 = 0.1 and 0.5 for manure and enteric fluxes, respectively. Hristov et al () further developed a county‐level emission inventory based on animal population, with some of the largest discrepancies relative to existing inventories occurring over our study region, the Upper Midwest.…”
Section: Introductionmentioning
confidence: 99%
“…Hristov et al () showed that current inventories differed significantly in their spatial allocation of agricultural methane emissions: within the contiguous United States, the Emission Database for Global Atmospheric Research v4.2 FT2010 (EDGAR, ) and Gridded Environmental Protection Agency (EPA) (Maasakkers et al, ) estimates correlated to only R 2 = 0.1 and 0.5 for manure and enteric fluxes, respectively. Hristov et al () further developed a county‐level emission inventory based on animal population, with some of the largest discrepancies relative to existing inventories occurring over our study region, the Upper Midwest. Furthermore, a recent study based on tall tower measurements in the U.S. Upper Midwest concluded that livestock methane emissions were underestimated 1.8‐fold in the Gridded EPA inventory (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Top-down inventory estimates are based on inverse modeling and use gridded bottom-up (BU) inventories as prior estimates. Thus, errors associated with gridded BU inventories can lead to errors in the TD inventory (Hristov et al, 2017); this makes TD estimates not ideal to evaluate US EPA methodology. Measurements of facilities that provide activity and management data avoid this potential error, and thus are more suited to evaluate US EPA methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Perhitungan emisi metana dari kotoran ternak jauh lebih rumit dibandingakan dengan emisi metana dari ruminansia karena terkait dengan komposisi kotoran ternak, tipe fasilitas penyimpan kotoran ternak, sistem perkandangan, berapa kali hewan mengeluarkan kotoran dan suhu lingkungan merupakan contoh faktor yang sulit untuk di inventarisir (Hristov et al, 2017). Kemudian, pentingnya perhitungan inventarisasi emisi dari sektor peternakan harus dilakukan setiap tahun dengan tidak menggunakan faktor emisi yang konstan karena meningkatnya laju populasi ternak dan sistem manejemen perkandangan yang semakin maju (Yu et al, 2018).…”
Section: Pendahuluanunclassified